EFFECT OF AGAR AND KAPPA-CARRAGEENAN ON THERMAL AND MECHANICAL PROPERTIES OF THERMO PLASTIC STARCH (TPS) - Akbar Hanif Dawam Abdullah; Putri Putih Puspa Asri; Rossy Choerun Nissa; Dina Fransiska; Nurhayati Nurhayati; Agusman Agusman; Hari Eko Irianto; Panji Priambudi; Sri Marliah (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
Effect of Agar and kappa-Carrageenan on Thermal and Mechanical Properties of Thermo Plastic Starch (TPS) Thermoplastic starch needs to be blend with other materials because of its limited properties. In order to gain the desired properties, the interaction between the added component (filler, plasticizer, second polymer, etc) must be concerned as it can affect the performances of the final product. Thermoplastic starch has been successfully made with mixing and compression molding with the addition of agar and kappa-carrageenan. The effect of the added material has been studied with FTIR, Tensile, DSC, and TGA to investigate their mechanical and thermal properties. The FTIR spectrum has shown the shifting around the methyl group (C-H), a carboxyl group (C-O), and a hydroxyl group (O-H). Thermal analysis results presented different patterns in melting and degradation behavior. The tensile strength value did not show significant improvement with the presence of agar and kappa-carrageenan. It is shown that the addition of agar and kappa-carrageenan affects thermal behavior but does not significantly impact the mechanical properties.